Statistical learning models to measure the impact of COVID-19 on financial fragility - Agosto, Arianna; Giudici, Paolo; Tanda, Alessandra (Frontiers in Artificial Intelligence, 2024)
This paper investigates the effects of the economic shock produced by the COVID-19 outbreak and diffusion on households'. Through a survey administered to Italian households, without loss of generality, we investigate changes in financial and economic decisions and the households' ability to cope with daily purchases, repay their debt obligations and face unexpected expenses. The paper also applies a statistical learning model through a synthetic indicator for the financial vulnerability of households, integrating the relevant information on the financial literacy and education of the surveyed individuals.